Listeria exploits IFITM3 to suppress antibacterial activity in phagocytes - Joel M. J. Tan (Nature Portfolio, 2021)
Interferon (IFN) is an important component of antiviral immunity, but can also be exploited by bacteria for immune evasion. Here the authors show that Listeria monocytogenes (Lm) induces type I IFN to suppress the degradation of Lm virulence proteins, ActA and LLO, and promote Lm infection in an IFITM3-dependent manner, thereby hinting at a potential target for antimicrobial therapy.